Trilhos e memória: preservação do patrimônio ferroviário em Minas Gerais - Monica Elisque do Carmo (2014)
This study presents a brief history of the implementation of railroads in Brazil and the formation of the Rede Ferroviária Federal Sociedade Anônima (Federal Joint-Stock Rail Network), (RFFSA) - the Brazilian state-owned railway company, founded in 1957 and dissolved in 2007. It was given to the National Historic and Artistic Heritage Institute (IPHAN) through the law numbered 11.483/07 the role of preservation and dissemination of the Railway Memory that would be done through the administration, safekeeping, storage and maintenance of movable or immovable assets that are valuable artistically, historically and culturally that will be fulfilled, among other functions, by the construction, organization, maintenance and expansion of museums, libraries, archives and other cultural organisations including the collections and acquis. If these assets are considered as operational ones they shall be shared. This present study also addresses to the importance that is to preserve the document records, the actions developed until now by IPHAN in Minas Gerais and the absolute necessity of a lengthy discussion among the numerous institutions that are involved in the memorys preservation, the cultural heritage surveillance and in teaching and research at a municipal, state and national level aiming at the creation and organisation of Railway Memory Centres. In order to achieve its aims this present thesis, raises questionings about the management and the sharing of the information regarding the railway heritage, through the usage of the international regulation applied to Librarianship, Archives Management and Museum Sciences, and also to the contribution of the Information and Communication Technologies in order to preserve, disseminate and access the railway archives. This study also points out what are the internal difficulties IPHAN faces while managing the documented records and how this will reflect on the unequal treatment the actions of preservation of the railway heritage receive. This study also focuses on how important is the creation of a Master Plan based on discussions and multidisciplinary research with regard to the creation of the Railway Memory Centre after having its archives recovered.